Healthcare providers' knowledge, attitudes, and perceptions from using targeted sequencing to diagnose and manage drug-resistant tuberculosis (DR-TB) in Eswatini. - Maia Madison; Debrah Vambe; Sein Sein Thi; Mangaliso Ziyane; Nosisa Shiba; Babongile Blisset Nkala; Tara Ness; Agostinho Viana Lima; Sindisiwe Dlamini; Siphiwe Ngwenya; Anna Mandalakas; Alexander Kay (PLOS Global Public Health)
Challenges in diagnosing drug-resistant tuberculosis (DR-TB) contribute to a diagnostic gap. Design-locked Targeted Sequencing (TS) assays have the potential to improve DR-TB diagnosis and management. TS assays are now being introduced into low-income, high TB burden settings. Eswatini is among the first high burden countries to have implemented TS for patient care. To evaluate the impact of the current program and optimize future implementation, we evaluated healthcare provider knowledge, attitudes, and perceptions (KAP) of TS and its implementation. We conducted semi-structured interviews with healthcare providers. Interviews were continued until data saturation was reached and analyzed by directed thematic analysis. The study was conducted at 85% of all DR-TB treatment centers (12/14) in rural and urban settings across all four regions in Eswatini. We interviewed nine doctors and eight nurses who were purposively sampled from DR-TB care sites in Eswatini. We found that providers' experience, roles, and settings informed their knowledge and perceptions of DR-TB diagnosis and management. While all healthcare providers wanted to improve comprehensive drug susceptibility testing, operational challenges with the existing program shaped their KAP of TS. In some instances, providers reported that results from TS on sputum improved their ability to provide quality DR-TB patient care. However, they perceived a need for improvements in the delivery of TS results and desired more training to inform their current use of results from sputum and potential future use of results from stool. Overall, healthcare providers recognized TS as an important new tool with the potential to improve DR-TB patient care. However, they also recognized the need for additional healthcare worker training, community engagement, forecasting to avoid reagent shortages, and enhanced medical information systems. Investments in these areas would likely support more effective and sustainable implementation in Eswatini and other LMICs with high TB burdens.